2018
DOI: 10.1016/j.neuron.2018.09.010
|View full text |Cite|
|
Sign up to set email alerts
|

Vascular and Neurogenic Rejuvenation in Aging Mice by Modulation of ASM

Abstract: Highlights d ASM activity is upregulated in brain and/or plasma of aged humans and mice d Brain endothelial cell is a main contributor of increased ASM in aging d Increased ASM in aging causes BBB impairment and neuronal dysfunction d It is regulated by caveolae-mediated transcytosis and ERM dephosphorylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 56 publications
1
89
0
Order By: Relevance
“…ASM can also be preferentially transported to the outer leaflet of the cell membrane and secreted into the extracellular space during cellular stress and disease 29,30 . Previous studies have reported that the expression and activity of ASM change with age [45][46][47] . Thus, in this section, we review the critical roles of ASM in association with aging-related dysfunctions in physiological processes.…”
Section: Role Of Asm In Agingmentioning
confidence: 96%
“…ASM can also be preferentially transported to the outer leaflet of the cell membrane and secreted into the extracellular space during cellular stress and disease 29,30 . Previous studies have reported that the expression and activity of ASM change with age [45][46][47] . Thus, in this section, we review the critical roles of ASM in association with aging-related dysfunctions in physiological processes.…”
Section: Role Of Asm In Agingmentioning
confidence: 96%
“…38 In addition, growing evidence has indicated that limited caveolae-mediated transcytosis maintains BBB integrity in the CNS, 44 and BBB disruption due to increased vesicle transport has been confirmed in many models. 27,45 Cav-1 is a major structural component of caveolae and is mainly expressed in the vessels of the CNS. 46 Umesalma et al reported that Ang Ⅱ increases the expression of Cav-1 in the CNS in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB integrity assay was as previously described . Briefly, dextran (3 kDa, Invitrogen; D3328)was injected into the tail vein after 28 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations